Ventilator Associated Pneumonia (VAP): a retrospective review of all children diagnosed with a VAP during 2017 and 2018, in the PICU, Red Cross War Memorial Children's Hospital. - van Wyk, Liana (Department of Paediatrics and Child Health, 2022)
Background: Ventilator Associated Pneumonia (VAP) is a common hospital acquired infection in children leading to an increase in morbidity and mortality. A study conducted in our PICU in 2013, showed that VAP rates decreased dramatically after implementation of a VAP bundle and appointing a VAP coordinator, to 4/1000 ventilator days. As part of a “Plan, Do, Study, Act” cycle, it was necessary to evaluate the efficacy of these interventions. Objectives: To evaluate the VAP rate in the PICU over a two year period from 2017 - 2018, and secondly to describe the causative organisms and antibiotic sensitivity/resistance patterns during this period. Methods: This was a retrospective, descriptive study using the existing PICU VAP database to identify cases. Additional information was retrieved from the PICU admission database as well as clinical folders. Results: Over the 2 years, 31 VAP cases were identified. The VAP rate in 2017 was 4.0 /1000 ventilator days and 5.4 /1000 ventilator days in 2018. Compliance with the VAP bundle was 68% in 2017 and 70% in 2018. The median(IQR) duration of ventilation in 2017 was 9 (6-12) days and 15 (11-28) days in 2018. The median(IQR) length of PICU stay in 2017 was 11 (8 – 22) days and 25 (17-37) days in 2018. The most common cultured organism was an ESBL Klebsiella pneumoniae sensitive to Amikacin and carbapenems. Conclusion: Our VAP rate has not decreased further since 2013. The VAP rate was slightly higher in 2018, and it is imperative that we improve compliance with the VAP bundle, in order to reduce VAP rates. Klebsiella pneumoniae and Pseudomonas aeruginosa were the commonest organisms causing VAPs and empiric use of Piptazobactam and Amikacin is still appropriate.